2022
DOI: 10.48550/arxiv.2205.12407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convolutional Neural Processes for Inpainting Satellite Images

Abstract: The widespread availability of satellite images has allowed researchers to model complex systems such as disease dynamics. However, many satellite images have missing values due to measurement defects, which render them unusable without data imputation. For example, the scanline corrector for the LANDSAT 7 satellite broke down in 2003, resulting in a loss of around 20% of its data.Inpainting involves predicting what is missing based on the known pixels and is an old problem in image processing, classically bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Context-based meta-learning, also referred to as Neural Processes (NPs), has been emphasized since it can properly predict unseen data inputs without huge computation costs [6]- [8]. Many papers have shown that the context-based meta-learning algorithms are effective not only for synthetic regression, image-inpainting, and few-shot classification but also for reinforcement learning [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Context-based meta-learning, also referred to as Neural Processes (NPs), has been emphasized since it can properly predict unseen data inputs without huge computation costs [6]- [8]. Many papers have shown that the context-based meta-learning algorithms are effective not only for synthetic regression, image-inpainting, and few-shot classification but also for reinforcement learning [9]- [11].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, those gain better performance by constructing the context representation that considers the relationship between corresponding features from all the given context data points. To also acquire the translation invariance, convolutional neural processes employed convolutional neural networks and a kernel density estimation method with equally spaced additional data points for functional context representation [11], [14], [15]. Moreover, for noise invariance, [12], [16] proposed to apply bayesian approaches such that the bayesian aggregated function and bootstrapping method are used to improve robustness against irreducible noises.…”
Section: Introductionmentioning
confidence: 99%
“…However, the vast majority of classical deep learning methods require a huge amount of training data to assure effective convergence of the model parameters. Convolutional conditional neural processes (ConvCNPs) and convolutional latent neural processes (ConvLNPs) have been shown to exhibit very good few-shot and zero-shot learning capabilities [ 24 ], but these methods still need pretrained models.…”
Section: Introductionmentioning
confidence: 99%